The formation of ordered clusters in Ti–7Al and Ti–6Al–4V. (15th June 2016) - Radecka, A.; Bagot, P.A.J.; Martin, T.L.; Coakley, J.; Vorontsov, V.A.; Moody, M.P.; Ishii, H.; Rugg, D.; Dye, D.
Abstract: TiAl alloys can suffer from a chemical decomposition on ageing around 500°C or on air cooling. At long ageing times this results in the formation of α 2 (Ti3 Al) precipitates. At reduced times or elevated temperatures, diffuse electron or neutron diffraction peaks can be observed, which has been termed 'short range ordering' (SRO). Here, we present correlative transmission electron microscopy (TEM) and atom probe tomography (APT) results showing that the reaction proceeds through the formation of ordered Al-rich precipitate clusters. Notably, Al–Al clustering could be observed well before the appearance of distinct precipitates in the TEM. In addition, the V-containing α phase of Ti–6Al–4V formed ordered clusters much faster than in binary Ti–7Al. This implies that the ternary addition of β stabilisers exacerbates the problem of α 2 precipitate formation in commercial dual phase titanium alloys. Graphical abstract: